Interpreting Religious Values in the Singer Tungkun Tradition Among the Dayak Community in Central Kalimantan - Suriadi, Suriadi; Emzaed, Ali Murtadho; Ibrahim, Bukhari (IAIN Palangka Raya, 2024)
The research is motivated by the increasing number of cases of domestic problems caused by the presence of third parties, resulting in divorce cases, therefore the presence of the singer tunkun is an effort to increase legal awareness in the community so that they obey and respect existing Dayak traditional religious values and instill awareness. Customary living based on religious teachings is always emphasized so that divorce and cases of the presence of third parties in domestic relationships do not occur again. The research aimed to explore the religious values found in singer tungkun among the Dayak people of Central Kalimantan. The method used phenomenological research using collaboration from interviews and literature review surveys. The results showed similarities between the religious values in the tradition of singer tungkun with the religious values, contained in the Islamic religion, namely being devoted to God Almighty, being fair, deciding everything through deliberation, forgiving each other, and living peacefully in unity and not mutual enemies, and do not betray each other.